47 Important outcomes to measure in trials of touch-based complementary therapies in palliative care. (30th January 2023) - Mitchinson, Lucy; Candy, Bridget; Kupeli, Nuriye; Vindrola-Padros, Cecilia; Robinson, Diana; Boland, Jason W; Stone, Patrick
Abstract : Introduction: Complementary therapies, such as massage and reflexology, are widely used in palliative care settings. People with advanced disease report a range of physical and psychological benefits, however clinical trials evidence for effectiveness of complementary therapy is inconclusive. Developing a core outcome set (a list of outcomes deemed most important by key stakeholders) can ensure clinical trials consistently evaluate meaningful outcomes. Aims: To develop a core outcome set for touch-based complementary therapies in palliative care. Methods: Potentially relevant outcomes were identified by screening published randomised control trials of touch-based therapies in clinical populations identified in a systematic review, and qualitative studies of complementary therapies in people with advanced disease. Semi-structured interviews were conducted with patients and complementary therapists to identify additional relevant outcomes. Patients, complementary therapists and academics rated the importance of the identified outcomes in a modified online Delphi survey. Outcomes for which ≥70% of the group agreed were critically important and were discussed and voted on in a consensus meeting. Results: 59 unique outcomes were identified from published literature and interviews. Of these, 17 were deemed critically important in the Delphi survey. From voting in the consensus meeting, five outcomes were selected for inclusion. An additional three outcomes were identified as important to patients and were incorporated. The final core outcome set comprises; Anxiety, Sleep quality, Overall mental wellbeing, Pain, Muscle relaxation, Mental resilience, Enjoyment and Patient satisfaction. Conclusions: A Core Outcome Set reflecting the priorities of patients, complementary therapists and academics has been developed to be used in palliative care clinical trials. Impact: Use of the core outcome set in future trials will standardise outcomes and allow for better data comparison and synthesis. Improving the evidence base will help us bridge the gap between patient experience and trial outcomes and better understand the effect of complementary therapies for patients receiving palliative care.